Transparent PZT Capacitors on Glass for Actuating Applications - Franklin Pavageau; Christel Dieppedale; Kevin Benedetto; Christophe Licitra; Laurent Frey; Fabrice Casset; Gwenaël Le Rhun (Proceedings)
Fully integrated transparent ITO/PZT/ITO capacitors on glass were obtained thanks to a recently developed wafer-to-wafer layer-transfer process to bypass the thermal budget issue associated with the high crystallization temperature of PZT (~700 °C). The fabricated devices show an average transparency of around 80% (and up to 94%) in the visible spectrum thanks to the use of SiO2 passivation acting as an anti-reflector and a transverse piezoelectric coefficient of up to 10.25 C/m2, which is suitable for the actuating purpose. The actuation of a vibrating glass plate (3.12 cm × 3.12 cm) was highlighted using a PZT capacitor (35.9 mm2) in agreement with the modeling.